SWAT 110: Printing the primary outcomE on Pink PapER versus standard paper to increase participant engagement to postal questionnaires (PEPPER). Issue 2 (March 2022) - Ooms, Alexander; Parsons, Scott; Dutton, Susan; Garrett, Angela; Fordham, Beth; Hing, Caroline; Lamb, Sarah E; Smith, Toby
Background: Missing data is a common issue in randomised controlled trials. There is a need to rigorously test means of participant retention. This embedded trial aims to examine the effect on postal response rates of printing a randomised controlled trial's primary outcome on pink versus white paper. Methods: Our randomised Study Within A Trial (SWAT) was run within a behaviour-change intervention host trial for patients following hip or knee replacements. Participants were randomised to receive the host trial's primary outcome measure printed on either a sheet of pink or white paper within the 11 sheet (21 page) 6-month follow-up questionnaire. The SWAT's primary outcome was host trial primary outcome measure completion. Number of reminders sent, proportion of remaining questions completed and overall questionnaire returns were secondary outcomes. Results: 176 participants were randomised: 88 received pink paper, 88 white paper. Host trial primary outcome measures were returned by 84.1% (74/88 participants) in the pink paper group and in 90.9% (80/88 participants) in the white paper group (risk ratio, 0.92 (95% CI 0.80, 1.06); p = .24). Reminders were sent to 48.9% (43/88 participants) in the pink paper group and in 30.7% (27/88 participants) in the white paper group (risk ratio 1.59 (95% CI 1.09, 2.33); p = .01). No other results were statistically significant. Conclusion: Printing the primary outcome on pink paper does not increase data return. From this small randomised study, there is some evidence that it potentially decreases response and is more burdensome to collect postal data by increasing the necessity for reminders.